2019
DOI: 10.11613/bm.2019.030705
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of minimum retesting intervals in managing repetitive laboratory testing: experience from a Croatian university hospital

Abstract: Introduction: Inappropriate laboratory retesting can be addressed by implementing minimum retesting intervals (MRI). The aim of our study was to assess the effectiveness of the implemented MRI protocol for inpatients. Materials and methods: Minimum retesting intervals were applied for 53 laboratory tests. The overall reduction of test requests, reduction in charges and reagent cost savings, frequency of MRI alert appearance as well as the rate of MRI acceptance and ignorance were calculated for a one-year peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The laboratory set turnaround time for test results was 60 min. According to available guidelines, minimum PCT retesting interval was set within the hospital laboratory order entry system at 24 h [25].…”
Section: Methodsmentioning
confidence: 99%
“…The laboratory set turnaround time for test results was 60 min. According to available guidelines, minimum PCT retesting interval was set within the hospital laboratory order entry system at 24 h [25].…”
Section: Methodsmentioning
confidence: 99%
“…In the observational period of six months, 22% of the orders generated an alert and 77% of these tests were cancelled. Lapić et al [ 29 ] implemented an MRI for inpatients at a university hospital for 53 tests. The pop-up alert gave information about the inappropriateness, referred to the date as well as the status of the previous test request and included the possibility to override the warning.…”
Section: Possible Strategies To Avoid Inappropriate Test Utilizationmentioning
confidence: 99%
“…Only a minority of surveyed clinicians stated that cost information frequently influenced their decisions. In general, cost control is endorsed by clinicians, but reductions in expenditure may be also achieved by implementing DM strategies, which combat overutilization [ 14 , 16 , 17 , 19 , 21 , 26 , 28 , 29 , 30 , 31 ].…”
Section: Possible Strategies To Avoid Inappropriate Test Utilizationmentioning
confidence: 99%
“…31 A study performed within a laboratory of a university hospital in Croatia showed that standardizing minimum intervals for performing tests could lead to a significant reduction (approximately 50%) in TM test orders, and consequently to a reduction in overall costs. 32 Similarly, Torre et al (2015) indicated that the number of adequately requested TMs increased from 31 to 78% once their utilization protocol was standardized. 33 Educational programs directed at primary care physicians could lead to a reduction of up to 51% in performed tests (TMs or not), saving approximately US$ 60 000 per year.…”
Section: Discussionmentioning
confidence: 99%